Data sharing statements for clinical trials. (5th June 2017) - Taichman, Darren B; Sahni, Peush; Pinborg, Anja; Peiperl, Larry; Laine, Christine; James, Astrid; Hong, Sung-Tae; Haileamlak, Abraham; Gollogly, Laragh; Godlee, Fiona; Frizelle, Frank A; Florenzano, Fernando; et al.
Abstract : A requirement of the International Committee of Medical Journal Editors